Changes in the functional diversity of birds due to habitat loss in the Brazil Atlantic Forest - Mariano-Neto, Eduardo; Santos, Rafael A. S. (Frontiers in Forests and Global Change, 2023)
Habitat loss at the landscape scale can result in complex taxonomic and functional diversity changes. Meanwhile, changes in the functional diversity reflect the modifications in the ecosystem functions, patterns of resources' use, and interactions. We evaluated how habitat loss at a landscape scale influences the functional diversity for different sets of bird communities (total community, frugivorous and insectivorous birds) in landscapes from 5% to 60% of forest cover at the landscape scale in the Bahia Atlantic Forest. We sampled twelve 6 x 6 km landscapes in a gradient of forest cover, with a sample design that aimed to minimize some landscape-scale bias. In each landscape, we surveyed eight plots randomly located in forested areas. We focused on forest-dependent species and measured the species richness and relative abundance. We chose 19 functional traits to evaluate functional diversity for the total community, 11 traits for the frugivore birds, and 12 traits for the insectivore birds. The choice of traits represents how species used their resources and were also used in other studies. Functional diversity was accessed through three different metrics: FRic, FEve, and FDiv. We also evaluated the response pattern of bird functional diversity using model selection and the response models null, linear, and logistical. Our results indicated that as forest amount decreased, there was a sharp decrease in FRic, especially below 30% forest cover. It also indicates a reduction in the use of resources by species in those landscapes. FEve showed a sharp decrease in landscapes below 15% of habitat, indicating a possible decrease in structural complexity. Fdiv also decreases dramatically in landscapes below 15% of forest amount, which indicates a decrease in functional dissimilarity between species, probably due to environmental filtration, which can lead to taxonomic homogenization. We assessed the importance of forests to provide the resources for species persistence and their functions, besides population sources. Our study showed quantitative indicators of the relationship between functional diversity and habitat loss, an essential element to implementing more robust conservation actions to preserve Atlantic Forest and its ecosystem services throughout time.